Prevision of multidisciplinary head and neck cancer survivorship care during the 2019 novel coronavirus pandemic. Issue 7 (18th May 2020) - Nilsen, Marci Lee; Clump, David A.; Kubik, Mark; Losego, Karen; Mrozek, Alyssa; Pawlowicz, Elizabeth; Pickford, Debra; Sridharan, Shaum; Traylor, Katie; Wasserman‐Wincko, Tamara; Young, Kelly; Zandberg, Dan; et al.
Abstract: The 2019 Coronavirus Pandemic challenges the delivery of care for patients with head and neck cancer. An important aspect of this care has been the evolution of enhanced survivorship services, which include surveillance for recurring cancer and prevention of second primaries. The application of evidence‐based approaches to the identification and management of treatment and tumor‐related toxicities has embraced the use of validated patient‐reported outcomes instruments, health promotion, and care coordination. In this manuscript, we describe how our multidisciplinary team of survivorship providers has accommodated to the need to provide patients with social distancing while acknowledging the importance of continued care during treatment and through the spectrum of survivorship.